Community pharmacists workforce readiness to deliver vaccination services: A cross‐sectional study from Jordan. Issue 2 (3rd March 2022) - Alnahar, Saja A.; Gkountouras, Georgios; Darwish, Rula M.; Bates, Ian
Abstract: This study assesses Jordanian community pharmacists' readiness and willingness to deliver vaccination services in their practice sites. Between February and April 2021, a self‐administered online questionnaire was distributed via social media, WhatsApp messages, and personal communication. The questionnaire targeted practicing community pharmacies. Descriptive and inferential data analysis was carried out. A total of 403 community pharmacists participated in the study. Almost 146 (36%) community pharmacists reported vaccinating patients in their practice sites. However, readiness assessment revealed that only 54 (13.4%) pharmacists received the required training and qualifications. Moreover, 33 (8.2%) study participants worked in adequately equipped and designed community pharmacies. Overall, surveyed participants held positive attitudes toward their involvement in vaccination services: 260 (64.5%) pharmacists were willing to vaccinate patients, and 227 (65.0%) out of unready, unqualified, participants were willing to get needed training and qualifications. According to study participants, regulatory and professional bodies (Ministry of Health, Jordan Pharmacists Association) are influential in supporting pharmacist‐vaccinators. Among the investigated factors, organizational structure and employment status were significantly associated with pharmacists' readiness to deliver vaccination. This study revealed that further work is needed to increase pharmacists' and pharmacies' readiness to deliver vaccination services and that regulators should follow a more active approach in highlighting the importance of training and the impact of training in patients' safety and satisfaction. Abstract : This figure briefly describes the study's population, design, and main outcomes.